ffect of castration and docking of lambs on maintenance behaviour and cortisol level - H.H. Emeash; A.S. Mostafa; N. M. Abdel-Azem (Journal of Veterinary Medical Research, 2018)
Thirty apparently healthy lambs with average weight and age of 5.8±0.5 kg and 15±1.6 days respectively were chosen in Sids Agricultural Research Station belonging to Animal Production Research Institute in Beni-Suef governorate to investigate the effect of castration and docking on maintenance behaviour and blood cortisol level during and after such operations. Lambs were classified into castration (n=10), docking (n=10) and control (n=10) groups. The results revealed that castration and docking could significantly affect the behaviours of standing idle, recumbency, sleep, suckling and ingestion in lambs. Moreover, blood cortisol level was significantly (p<0.05) increased after operation in castrated and docked lambs as compared to the time before, at operation and 3 hours after operation.